Contract Farming of Ginger in Nepal, 2014 - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The data is collected through a primary field survey of around 600 ginger-cultivating farm households in Nepal, using a structured questionnaire. It aims at identifying the determinants of participation in contract farming of ginger in Nepal and assess impact of contract on farmers’ profits and adoption of food safety practices at farm-level. The data includes farm and farmer characteristics, cropping pattern, economics of cultivation, marketing channels, and good agricultural practices. The survey was conducted during December 2014 in the hill districts of Pyuthan, Palpa, and Arghakhanchi, located in the Western and Mid-western development regions of Nepal. These districts were chosen due to high concentration of contract farmers there. The sample comprises 322 contract farmers and 283 noncontract farmers.